Meningkatkan Keaktifan Siswa Kelas IV Fase B dalam Pembelajaran Agama Katolik Melalui Model Problem-Based Learning (PBL) di SDN 15 Teluk Pongkal - Dedy Murdani (Sekolah Tinggi Pastoral Kateketik (STPKat) Santo Fransiskus Assisi Semarang, 2024)
This study aims to enhance the activity of fourth-grade students in Phase B of Catholic Religious Education at SDN 15 Teluk Pongkal through the implementation of the Problem-Based Learning (PBL) model. PBL was chosen because it encourages students to think critically and actively participate in the learning process. In this learning approach, students are engaged in solving problems that are relevant to their daily lives. The research findings indicate that the average test score of students significantly improved from 69 in Cycle 1 to 80 in Cycle 2. This increase reflects the effectiveness of the PBL model in enhancing the learning process. Additionally, the P3 observation data showed that student activity also rose, with an average of 53% in Cycle 1 and increasing to 67% in Cycle 2. Thus, the implementation of the PBL model not only improves students' academic scores but also strengthens their engagement in learning. Through this approach, students are expected to become more active, critical, and creative in addressing various problems they encounter. This study contributes significantly to the development of more interactive and engaging teaching methods, especially in the context of Catholic education.